Design of a 10-Ton Capacity Solar-Powered Cold Storage at the Cituis Fish Auction Site, Tangerang, Banten, Indonesia - Wardi, Wardi; Budiyanto, Muhammad Arif (Journal of Materials Exploration and Findings, 2025)
This study presents the design of a 10-ton capacity solar-powered cold storage system for the Cituis Fish Auction Site (TPI) in Tangerang, Indonesia, as a sustainable solution to support the coastal fisheries sector. The system comprises two temperature zones: an anteroom at 5°C and a freezer room at -30°C, both integrated with a hybrid system utilizing solar panels and batteries. The total power consumption of the cooling system reaches 27.51 kW. The simulation results, obtained using HOMER Pro software, indicate that the hybrid PV system can reduce CO2 emissions by up to 16,754 kg per year. From an economic perspective, the system shows high feasibility with a payback period of only 0.41 years, a capital expenditure (CAPEX) of IDR 745.29 million, and a monthly operational cost (OPEX) of IDR 9.7 million. These findings confirm that the system is both technically and economically viable and can be replicated in other coastal regions.